PENGARUH LIKUIDITAS, HUTANG, INVESTASI, PROFITABILITAS, DAN PERTUMBUHAN PERUSAHAAN TERHADAP DIVIDEN PAYOUT RATIO PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015-2018 - Ni Kadek Ida Pratiwi; Putu Wenny Saitri (Journal of Applied Management and Accounting Science, 2020)
Dividends are distributed to shareholders as earning after tax from company profit.The amount or percentage of profit taht a company will pay to shareholders as cash dividends is called the dividend payout ratio. The size of the dividend distributed by a company depends on the dividend plicy of the company, so it is necesarry to consider the comapny regarding the factors tha influence the dividend policy. The sample in this study was 34 manufacturing companies listed on the Indonesia Stock Exchange in 2015-2018.Determination of the sample using purposive sampling method. The analytical tool used is mutiple linear regression analysis. The result of the study using the t test showed that CR, DER, and investment had no significant effect on the dividend payout ratio, whereas ROE, had a positive ad significant effect on the dividend payout ratio. And company growth has negative effect on dividend payout ratio